Transgenic sorghum plants via microprojectile bombardment. - Casas, A M (1993)
Transgenic sorghum plants have been obtained after microprojectile bombardment of immature zygotic embryos of a drought-resistant sorghum cultivar, P898012. DNA delivery parameters were optimized based on transient expression of R and C1 maize anthocyanin regulatory elements in scutellar cells. The protocol for obtaining transgenic plants consists of the delivery of the bar gene to immature zygotic embryos and the imposition of bialaphos selection pressure at various stages during culture, from induction of somatic embryogenesis to rooting of regenerated plantlets. One in about every 350 embryos produced embryogenic tissues that survived bialaphos treatment; six transformed callus lines were obtained from three of the eight sorghum cultivars used in this research. Transgenic (T0) plants were obtained from cultivar P898012 (two independent transformation events). The presence of the bar and uidA genes in the T0 plants was confirmed by Southern blot analysis of genomic DNA. Phosphinothricin acetyltransferase activity was detected in extracts of the T0 plants. These plants were resistant to local application of the herbicide Ignite/Basta, and the resistance was inherited in T1 plants as a single dominant locus.